What's Your Child Worth? An Analysis of Expected Dowry Payments in Rural India. (June 2020) - Maertens, Annemie; Chari, A.V.
Highlights: We introduces a new primary dataset on dowry payments in rural India. We asked parents about actual dowry payments and expected dowry payments. The actual and expected dowry payments are consistent with each other. Individual characteristics of the bride are significantly more important in explaining expected dowries compare to household characteristics. Abstract: This paper introduces a new primary dataset on dowry payments in rural India. A novel feature of the data is that in addition to eliciting actual dowry payments, we also asked rural Indian households how much dowry they expected to pay/receive for each of their currently unmarried children. These expectations are presumably the basis of household decision making (as opposed to actual dowries paid and received) with respect to decisions such as human capital investments, saving and consumption, etc. We find that the distribution of dowry forecasts appears to be consistent with the distribution of actual dowry payments, suggesting that dowry perceptions may be quite accurate. Our analysis of dowry forecasts further indicates that (i) individual-specific attributes are significantly more important than household income and wealth in terms of explaining the magnitude of dowry payments, and (ii) bride quality is also a significant determinant of dowry, which provides a corrective to the emphasis on groom quality in the literature.